2018
DOI: 10.1111/jtxs.12337
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of sodium chloride by salt microspheres in dough: Effect on dough rheological properties

Abstract: The different salt types (table-Ts, sea-Ss and hollow microsphere-Hs) which were studied in our work differ just slightly. However, an important issue in choosing salt should also be the nutritive perspective, in particular low sodium content as a preventive measure against cardio-vascular diseases. Hs and Ss are therefore suitable alternatives to typical Ts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The punch test method, which was originally proposed by Manahan, Argon, and Harling [ 16 ], was used to characterize metal elements in the power industry. Currently, this method is used and developed for different branches such as the evaluation of plastic properties [ 17 ] or in the evaluation of powder materials such as milk powder [ 15 ] or sucrose [ 12 ], as well as modifications of this method based on the same principle of operation are used for hardness and texture testing [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The punch test method, which was originally proposed by Manahan, Argon, and Harling [ 16 ], was used to characterize metal elements in the power industry. Currently, this method is used and developed for different branches such as the evaluation of plastic properties [ 17 ] or in the evaluation of powder materials such as milk powder [ 15 ] or sucrose [ 12 ], as well as modifications of this method based on the same principle of operation are used for hardness and texture testing [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, substituting 0.15%–0.4% of NaCl by sea salt and commercial SS (SODA‐LO Fine Salt™) resulted in the significantly softer ( P < 0.05) yeast‐leavened dough than NaCl (Král et al ., 2018). The reduction in hardness was due to the substitution of NaCl‐weakened gluten protein conformation and contributed to the higher water absorption by the dough.…”
Section: Salt Substitutesmentioning
confidence: 99%
“…Similarly, Larsson (2002) reported an increase in G ′ with an increase in NaCl addition whereas McCann and Day (2013) found no significant differences in the G ′ values of doughs containing 0, 1, or 2% NaCl. Beck, Jekle, and Becker (2012) found both G ′ and dough stickiness values to increase with an increase in dough salt concentration whereas Král et al (2018) reported dough stickiness values to decrease with a small increase in sea salt concentration from 0.15 to 0.40%. In all the aforementioned studies, large deformation analyses indicated a strengthening effect of NaCl addition.…”
Section: Introductionmentioning
confidence: 99%